Oil and non-energy commodity markets: An empirical analysis of volatility spillovers and hedging effectiveness - Anupam Dutta; Md Hasib Noor (Cogent Economics & Finance, 2017)
Although a large number of empirical papers have examined the price spillover in global oil and non-energy commodity markets, very little is known about the volatility transmission between these two markets. The present study aims to conceal this gap by investigating the volatility cross effects between oil and three different non-energy commodity markets. Using the bivariate VAR-GARCH models, we do not find any evidence of volatility linkage between oil and agricultural product markets during the sample period used. We, however, document that oil market sends volatility to both metal and non-energy aggregate markets. This finding is not surprising, since petroleum-related products are one of the major production inputs in metal industries and hence the production process of metals largely depends on the crude oil market. Since various financial assets are traded on the basis of commodity markets, our results are beneficial for portfolio diversification and hedging decisions. Policy-makers could also use the findings of this research to reduce the impact of oil price uncertainty on metal and agricultural markets.
Keywords: 330; oil market; non-energy commodity markets; volatility transmission; hedging effectiveness; VAR-GARCH model